COLLECTIVE LEADERSHIP IN ISLAMIC BOARDING SCHOOLS: A MULTI-SITE STUDY AT SUMBER PAYUNG AL AFIQI, AL HASYIMI, BABUSSALAM, AS SYUKRI, AND ATTABRANI - A Hufron; Abd. Hannan; Abdul Wahid (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
The Sumber Payung Ganding Sumenep Islamic Boarding School consists of five branches: Al Afiqi, Al Hasyimi, Babussalam, As Syukri, and Attabrani. However, the lack of understanding regarding internal and external dynamics affects the effectiveness of collaboration among leaders. This study aims to examine the leadership model, leadership functions, and collective leadership characteristics at Sumber Payung Islamic Boarding School. The approach used is qualitative, with data collection through interviews, observations, and documentation. The research findings show that, first, Sumber Payung Islamic Boarding School implements a collective leadership model based on consensus, with variations in implementation across the branches. Second, leadership functions to enhance transparency, resolution accuracy, and more effective conflict management across all branches of the boarding school. Third, the characteristics of collective leadership vary according to the organizational structure and the involvement of leaders, with some branches demonstrating higher effectiveness due to structured management and strong external collaboration. The benefits of this study can provide insights into the application of collective leadership in improving the management of Islamic boarding schools more effectively.